Functionalized pineapple aerogels for ethylene gas adsorption and nickel (II) ion removal applications. Issue 6 (December 2020) - Lim, Zi En; Thai, Quoc Ba; Le, Duyen K.; Luu, Thao P.; Nguyen, Phuc T.T.; Do, Nga H.N.; Le, Phung K.; Phan-Thien, Nhan; Goh, Xue Yang; Duong, Hai M.
Graphical abstract: Highlights: Functionalized pineapple aerogel can be used for ethylene gas adsorption. Functionalized pineapple aerogel can be used for nickel ion removal. Functionalized pineapple aerogel is a promising candidate for heavy-ions removal. Functionalized pineapple aerogel is a promising candidate for food preservation. Abstract: Over 27 million tons of pineapples are produced globally annually, from which approximately 76.4 million tons of pineapple leaf by-product waste are generated. Even though the fibers within the pineapple leaves exhibit excellent properties, several efforts to repurpose pineapple leaf wastes have remained lack luster, with most farmers still disposing the waste to landfills or burning them in open fields. This work sets out to transform pineapple leaf fibers extracted from agricultural pineapple leaf waste into highly porous aerogel for high-value engineering applications to enhance the monetary incentive to repurpose agricultural waste. Pineapple aerogels are developed and functionalized with activated carbon and diethylenetriamine for ethylene adsorption and nickel ions removal applications, respectively. The modified aerogels maintain a porous structure with a porosity of 91.1–96.4% and density of 32.2–92.6 mg/cm 3 . Activated carbon coated pineapple aerogel exhibits excellent ethylene adsorption capability, with a maximum adsorption capacity of 1.08 mmol/g at atmospheric pressure, surpassing those of commercial ethylene absorbents (0.157 mmol/g). While diethylenetriamine coated pineapple aerogel shows its good nickel ion adsorption with maximum adsorption capacity of 0.835 mmol/g, as predicted by the Langmuir-Freundlich isotherm model. The results suggests modified pineapple aerogels are promising candidates for capturing ethylene in food preservation and nickel ions removal in wastewater.